Hawthorne’s Ego Defense Mechanism on “The Birthmark” - Herin Ratnaningsih (International Journal of Pedagogical Language, Literature, and Cultural Studies (i-Plural), 2024)
Nathaniel Hawthorne's "The Birthmark" is a rich embroidery of human psychology entwined to Puritan society. The following analysis examines human imperfection and the attempt to pursue perfection by employing the ego defence mechanism. In Hawthorne's "The Birthmark", Aylmer endures the anxiety and fear of intimacy that he leads to deny and projects Georgiana’s birthmark removal through scientific surgery. His fixation on her birthmark is also a way to unleash his scientific insecurity. Georgiana not only internalizes Aylmer’s ideals but also rationalizes the removal of the birthmark. This study exhibits Aylmer’s and Georgiana’s denial, repression, projection, idealization, and rationalization through the specific analysis.